2015
DOI: 10.1097/md.0000000000002166
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparisons Between Patients on Peritoneal Dialysis With and Without Polycystic Kidney Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…For the 9 studies [9, 16, 18-20, 22-24, 26] which examined the association of PD-related complications in PKD and non-PKD patients on PD, 7 studies [9,16,19,20,23,24,26] reported peritonitis, 6 studies [9,16,18,22,23,26] reported hernias and 5 studies [9,16,23,24,26] were leak. We found that there was no significantly statistical difference on PD-related complications in PKD and non- Fig.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…For the 9 studies [9, 16, 18-20, 22-24, 26] which examined the association of PD-related complications in PKD and non-PKD patients on PD, 7 studies [9,16,19,20,23,24,26] reported peritonitis, 6 studies [9,16,18,22,23,26] reported hernias and 5 studies [9,16,23,24,26] were leak. We found that there was no significantly statistical difference on PD-related complications in PKD and non- Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…The main features of the studies on the adverse outcomes for all articles in Table 1. 7 studies [16-19, 21, 24, 39] were conducted in Europe, with the exception of seven [9,20,22,23,25,26,40] conducted in Asia. Patients' age in PKD ranged from 35.4 to 63.6 years old, however, patients' age in non-PKD was higher than PKD, ranged from 46 to 61 years old.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether PD is a feasible option for patients with ADPKD remains controversial due to inconsistent results. [7][8][9][10][11][12][13][14][15][16][17][18][19] Some did report higher rates of complications, while others have reported that PD in this patient population is well tolerated, with no difference in technique difficulty. Furthermore, some observational data suggested that the prognosis of ADPKD patients on PD may appear to be better than, or at least equivalent to, ADPKD patients on HD 5,20 as well as those with other aetiologies of ESRD on PD.…”
mentioning
confidence: 99%